Stability analysis of water in oil emulsion in liquid membrane process - Othman, Norasikin; Sadikin, Aziatul Niza; Malini, Hemah (Faculty of Chemical Engineering & Natural Resources, 2008)

(untitled)
Emulsion liquid membrane (ELM) is one of promising technique in separation process. This process consists of three phases: an external phase, a membrane phase and an internal phase. The membrane phase physically separates the external and internal phases and contains a surfactant to maintain emulsion stability. In this project, the study has highlighted the importance of emulsion stability in emulsion liquid membrane process. The emulsion liquid membrane consist of Cyanex 302 as a carrier, kerosene as organic solvent, Span 80 as an emulsifying agent and sulphuric acid as stripping agent. The important factors studied which affect the ELM stability are emulsification time (4-20 min), agitation speed (200-400 rpm); the concentrations of surfactant (1-9 % w/v) and carrier (0.1 -0.9 M). The results showed that 3% w/v Span 80, 0.1 M Cyanex 302, 5 minute emulsification time and 350 rpm agitation speed is sufficient to form stable emulsion.